E3 ligase cIAP2 mediates downregulation of MRE11 and radiosensitization in response to HDAC inhibition in bladder cancer - Nicholson, J; Jevons, S; Groselj, B; Ellermann, S; Konietzny, R; Kerr, M; Kessler, B; Kiltie, A (American Association for Cancer Research, 2017)
The MRE11/RAD50/NBS1 (MRN) complex mediates DNA repair pathways, including double-strand breaks induced by radiotherapy. Meiotic recombination 11 homolog (MRE11) is downregulated by histone deacetylase inhibition (HDACi), resulting in reduced levels of DNA repair in bladder cancer cells and radiosensitization. In this study, we show that the mechanism of this downregulation is post-translational and identify a C-terminally truncated MRE11, which is formed after HDAC inhibition as full-length MRE11 is downregulated. Truncated MRE11 was stabilized by proteasome inhibition, exhibited a decreased half-life after treatment with panobinostat, and therefore represents a newly identified intermediate induced and degraded in response to HDAC inhibition. The E3 ligase cellular inhibitor of apoptosis protein 2 (cIAP2) was upregulated in response to HDAC inhibition and was validated as a new MRE11 binding partner whose upregulation had similar effects to HDAC inhibition. cIAP2 overexpression resulted in downregulation and altered ubiquitination patterns of MRE11 and mediated radiosensitisation in response to HDAC inhibition. These results highlight cIAP2 as a player in the DNA damage response as a post-transcriptional regulator of MRE11 and identify cIAP2 a potential target for biomarker discovery or chemo-radiation strategies in bladder cancer.